A New Real-Life Test for Reciprocity in Autistic Adults: The Interactive Drawing Test - Backer van Ommeren, Tineke; Vreugdenhil, Marianne; Koot, Hans M.; Spek, Annelies; Scheeren, Anke M.; Jertberg, Robert M; Begeer, Sander (Frontiers in Psychiatry, 2022)
Impaired social-emotional reciprocity is a defining feature of Autism Spectrum Disorder (ASD). Deficits in reciprocity can be difficult to assess, particularly in adults with average or above average intelligence. The recently developed Interactive Drawing Test (IDT) measures reciprocity in children and adolescents with and without ASD based on spontaneous non-verbal interactions during the joint creation of a drawing. In this study, we examined if the IDT is able to differentiate between 19 normally intelligent adults with ASD and 18 without ASD. The IDT total reciprocity score, including the number of meaningful contributions to objects initially drawn by the examiner, was lower in the autistic adults compared to those without ASD. By assessing both the quantity and quality of spontaneous reciprocal behaviour, the IDT was able to identify subtle differences in reciprocal behaviour of adults with and without ASD with average intelligence. Even though a larger sample is required to determine its psychometric properties, the IDT appears a promising tool to enrich the diagnostic process of ASD in adults.